Medication therapy of high‐dose methotrexate: An evidence‐based practice guideline of the Division of Therapeutic Drug Monitoring, Chinese Pharmacological Society. Issue 5 (8th February 2022) - Song, Zaiwei; Hu, Yang; Liu, Shuang; Wang, Guanru; Zhai, Suodi; Zhang, Xianglin; Li, Youping; Du, Guanhua; Shi, Yuankai; Chen, Yaolong; Dong, Mei; Guo, Ruichen; et al.
Abstract : Aims: A lot of medication risks related to high‐dose methotrexate (HDMTX) therapy still remain to be identified and standardized. This study aims to establish an evidence‐based practice guideline for individualized medication of HDMTX. Methods: The practice guideline was launched by the Division of Therapeutic Drug Monitoring, Chinese Pharmacological Society. The guideline was developed following the WHO handbook for guideline development and the methodology of evidence‐based medicine (EBM). The guideline was initially registered in the International Practice Guidelines Registry Platform (IPGRP‐2017CN021). Systematic reviews were conducted to synthesize available evidence. A multicentre cross‐sectional study was conducted using questionnaires to evaluate patients' perception and willingness concerning individualized medication of HDMTX. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was used to rate the quality of evidence and to grade the strength of recommendations. Results: Multidisciplinary working groups were included in this guideline, including clinicians, pharmacists, methodologists, pharmacologists and pharmacoeconomic specialists. A total of 124 patients were involved to integrate patient values and preferences. Finally, the guideline presents 28 recommendations, regarding evaluation prior to administration (renal function, liver function, pleural effusion, comedications, genetic testing), pre‐treatment and routine dosing regimen, therapeutic drug monitoring (necessity, method, timing, target concentration), leucovorin rescue (initial timing, dosage regimen and optimization), and management of toxicities. Of these, 12 are strong recommendations. Conclusions: We developed an evidence‐based practice guideline with respect to HDMTX medication using a rigorous and multidisciplinary approach. This guideline provides comprehensive and practical recommendations involving the whole process of HDMTX administration to health care providers.